A reliable ex vivo invasion assay of human reticulocytes by Plasmodium vivax. - Russell, B; Suwanarusk, R; Borlon, C; Costa, F; Chu, C; Rijken, M; Sriprawat, K; Warter, L; Koh, E; Malleret, B; Colin, Y; Bertrand, O; et al. (2011)
Currently, there are no reliable RBC invasion assays to guide the discovery of vaccines against Plasmodium vivax, the most prevalent malaria parasite in Asia and South America. Here we describe a protocol for an ex vivo P vivax invasion assay that can be easily deployed in laboratories located in endemic countries. The assay is based on mixing enriched cord blood reticulocytes with matured, trypsin-treated P vivax schizonts concentrated from clinical isolates. The reliability of this assay was demonstrated using a large panel of P vivax isolates freshly collected from patients in Thailand.